Study Results Suggest That Flavones and Flavan-3-ols Protect against Breast Cancer - Rizzo, Toni (MD Conference Express, 2014)
Consumption of fruits, vegetables, and carotenoids has been shown to reduce the risk of breast cancer, as they are rich in flavonoids. The objective of the Cancer Prevention Study II [CPS-II] Nutrition Cohort was to evaluate the association of several flavonoids on the risk of invasive breast cancer in women stratified by estrogen-negative status, as discussed in this article.